The predictable heartbreaks of Imogen Finch : a novel [large type] - Firkins, Jacqueline (Thorndike Press Large Print Softcover Romance and Women's Fiction, 2024)
"Imogen Finch has just been through her seventeenth breakup. She saw it coming, so she's not as crushed as she might be, but with all seventeen of her exes leaving her for other partners, she's come to believe a prediction her well-intentioned and possibly clairvoyant mother made over twenty years ago: that Imogen would never come first at anything or to anyone. Is her love life failing due to a magical curse? Insufficient effort? Poor timing or personality mismatches? Everyone has opinions on the matter. Imogen's ready to give up altogether. But when Eliot Swift, her secret high school crush, returns to their small coastal town after a decade of nomadic travels, Imogen has new motivation to try again. Eliot's full of encouragement. He suggests that her curse is not only imagined, it's easily breakable. All they need is one win--any win--and she can believe in love, and in herself again. From trivia games to swimming races to corn-shucking contests, the pair sets out to snag Imogen her first first. But when victory proves more elusive than Eliot anticipated, and when his deep-seeded wanderlust compels him to depart for far away places, Imogen fears she's destined to remain in second place forever. Fortunately for them both, sometimes magic lingers in the most unexpected places. And love is far from predictable"--